PENGARUH MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) BERBANTUAN GAMES EDUCATION TERHADAP HASIL BELAJAR SISWA KELAS IV PADA MATERI GAYA DAN GERAK - Rahmawati, Ima; Hayati Rahayu, Ai; Sadikin, Cecep (Buletin Ilmiah Pendidikan, 2023)
This research is motivated by the lack of variation in the learning process in the observed schools so that impact on student participation and low learning outcomes. The purpuso of this study was to investigate the effect of the Contextual Teaching Learning (CTL) model by wordwall games on the learning outcomes of fourth grade student in the material of Gerak dan Gaya. The research method is experimental one group pretes-posttes. The sample is 38 student. The instrument used is s cognitive test based on Bloom’s Taxonomy. The results of the study based on statistical test stated that CTL model had an effect on student learning outcomes as evidenced by the significant defference between pretes and posttest scores after applying the model.